The 21st century skills of the female students of practical education in the Department of Kindergartens in Faculty of Education - King Faisal University - Mohammad, Aidah Deep; Hussien, Asma Margeni (Advances in Social Sciences Research Journal, 2020)
This study aims at realizing the degree of acquiring the 21st century skills by the female students of practical education in the department of kindergartens at the Faculty of Education in the University ofKing Faisal , and ranking the acquisition of the skills by the female students . To achieve the objectives of the study , the researcher adoptedthe descriptiveanalyticalapproach , andthe application of the study’stool , namely thequestionnaire that consists of ( 40 ) items divided into five skills : 1 . Communication and participation . 2 . Informationculture . 3 . Lifeskills 4 . Learningand creativity . 5 . Emotional intelligence . Afterconfirming its validity and reliability , it was applied to the study’s sample , which consisted of ( 245 ) female students . The results showed that the degreeof acquiring the 21st century skills by the sample members was very high with an arithmetic mean ( 4 . 38 ) , and with a standard deviation ( 0 . 438 ) . The third field “ life skills “ was in the first place with an arithmetic mean ( 4 . 53 ) and a standard deviation ( 0 . 442 ) with a very high degree . The fourth field “ learning and creativity “ which was in the second place with an arithmetic mean ( 4 . 48 ) and a standard deviation ( 0 . 496 ) with a very high degree . The first field “ communication and participation “ was in the third place with an arithmetic mean ( 4 . 41 ) and a standard deviation ( 0 . 457 ) with a very high degree . The fifth field “ emotional intelligence “ was in the fourth place with an arithmetic average ( 4 . 26 ) and a standard deviation ( 0 . 632 ) with a very high degree . The second field “ information culture “ was in the last place with an arithmetic mean ( 4 . 23 ) and a standard deviation ( 0 . 561 ) with a very high degree . The study recommended the importance of incorporating the 21st century skills into the program for preparing kindergarten teachers , and working on developing professional development programs for the teacher in a way that suits the changesand developments of the current era .